Intersectionality of whiteness, racism, and homophobia among agriculture students. Issue 1 (2nd January 2022) - Martin, Michael J.; Hartmann, Katherine
ABSTRACT: This study looks to unearth bigoted ideas among White students in education classes at a large land-grant University. This research utilises Critical Whiteness in a narrative format to elicit 14 White education students' history of bigotry and its effect on their behaviour. Their stories highlight how White families and their friends talk about people of colour and members of the LGBTQ community in their White circles. While Whiteness studies traditionally focus on the discrimination against people of colour, this study found that many White students also talk about sexuality, class, and gender as necessary components to their White identity development. The strong bigoted views against members of the LGBTQ community by many of the students' families and even themselves warrant discussion of Whiteness as an intersection of multiple identities.